Peran Majelis Kehormatan Notaris (MKN) dalam Memberikan Perlindungan Hukum bagi Notaris Pengganti setelah Berakhirnya Masa Jabatan - Balyan Ibnu Mulkan Siregar; Hasim Purba; Suprayitno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Majelis Kehormatan Notaris (MKN) in providing legal protection for substitute notaries after the expiration of their term of office. The issues addressed include the limits of the legal responsibility of substitute notaries, the urgency of legal protection and the forms of protection provided by the MKN. This research employs a normative juridical method with statutory, conceptual and case approaches through library research. The findings indicate that substitute notaries remain legally responsible for deeds executed during their tenure. The MKN plays a significant role in providing protection through mechanisms such as approval for summons, legal assistance and supervision. Therefore, the MKN is essential in ensuring legal certainty and optimal professional protection for substitute notaries. In addition, reinforcing the capacity of the MKN is essential to enable the protection mechanism to function with greater efficacy and transparency, thereby ensuring enduring legal certainty for substitute notaries.